Biomass‐Derived Graphene‐Based Nanocomposites: A Futuristic Material for Biomedical Applications. Issue 5 (3rd February 2022) - Blessy Rebecca, P. N.; Durgalakshmi, D.; Balakumar, S.; Rakkesh, R. Ajay
Abstract: Advanced research in the field of material science and biomedicine leads to the development of materials that are efficient and cost‐effective. Graphene has been a widely studied material in recent years and graphene‐based materials exhibit exceptional properties that can be used for applications ranging from biomedical to electronics. In biomedical field, graphene‐based materials are employed in drug delivery, sensing, bioimaging and tissue engineering. However, the production of graphene from graphite and chemical precursors has certain drawbacks such as toxicity, expensive, complex fabrication process, etc. To overcome these, biomass have become a new source for graphene materials. Different types of biomass sources and various preparation methods for graphene‐based materials were reviewed. Here, the applications of biomass derived graphene‐based materials in biomedical field were discussed. Abstract : This article discusses recent developments in biomass‐derived graphene‐based nanostructures, with a focus on biomedical devices and applications. We went over all of the different methods for making graphene out of biomass, as well as the several possible uses in biomedical fields like biosensors, bioimaging, tissue engineering, drug delivery, and antibacterial agents.